IMPLEMENTASI PROGRAM EDUKASI DAN LATIHAN ERGONOMI UNTUK MENCEGAH LOW BACK PAIN PADA PEKERJA DENGAN AKTIVITAS DUDUK BERKEPANJANGAN DI LINGKUP UNIVERSITAS HALU OLEO TAHUN 2025 - HN, Muhammad Rustam; Mulyawati, Sufiah Asri; Ashaeryanto, Ashaeryanto; Zerbarani, Waode; Aulia, Audi; Ardiansyah, Ld Muh (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2025)
Low Back Pain (LBP) is one of the most common musculoskeletal problems among productive-age populations and remains a leading cause of reduced productivity and quality of life. Globally, more than 60–80% of individuals experience LBP at least once in their lifetime, while in Indonesia the prevalence reaches 38.4% within a three-month period among productive workers and 44.29% within 12 months. Among healthcare workers in Asia, the lifetime prevalence is reported at 58.1%. These high rates are closely associated with prolonged sitting, non-ergonomic working postures, improper workstation design, and the lack of regular stretching, all of which contribute to muscle tension and chronic pain. Similar conditions are observed at Universitas Halu Oleo, where academic and administrative staff spend 6–8 hours per day seated at desks or using computers, yet awareness of ergonomics and simple physical exercises remains low. Without appropriate intervention, this situation may lead to decreased work performance, increased functional disability, and higher healthcare costs. Therefore, an ergonomic education program combined with simple stretching exercises is urgently needed and feasible to implement within daily work routines. This program aims not only to enhance knowledge but also to foster sustainable healthy work behaviors, thereby reducing the risk of LBP, maintaining productivity, and supporting the development of a healthy and competitive work environment at Universitas Halu Oleo.